Storage effect on the moisture content (%) and sensory quality parameters of silver carp (Hypophthalmichthys molitrix) fish noodles and consumers’ preference to it - M. I. Hossain (Journal of Agriculture, Food and Environment, 2020)
Development of different fish products using boneless muscle is popular in this subcontinent. The present study was conducted to assess the changes in percent moisture content and sensory quality parameters of noodles prepared with silver carp mince along with wheat flour and to study the consumer’s preference to the fish noodles. Silver carp fish mince and other ingredients were incorporated with wheat flourin substitution levels of 0, 20, 25 and 30%. The prepared noodles were oven dried, cooled and stored in polythene and vacuum sealed packsduring storage at ambient temperature (30 to 35 °C) for 6 months. During this storage period no remarkable change could be observed in the color, flavor, texture and taste of the noodle samples accept the moisture content of the samples. The percent moisture content of noodle samples slightly increased (i.e., percent moisture content increased from 6.37 to 12.38 in sealed polythene pack after 90 days of storage and to 10.02 in vacuum sealed pack after 180 days of storage in control noodle sample whereas in sample with 30% substitution level of fish mince the value increased from 11.94 to 13.44 in sealed polythene pack andto 12.88 in vacuum sealed pack after 90 days and 180 days of storage, respectively) with the lapse storage period. No mold growth could be found on noodle samples. Fish noodles prepared with 25% silver carp mince had the highest score 7.9 (out of 9) for taste though scores for the color (7.9), flavor (7.8), texture (8.1) and overall acceptability (8.4) were higher for the noodles prepared with 30% silver carp mince. Therefore, the study could be concluded as-fish noodles can be stored at room temperature for about 6 months in polythene pack and vacuum sealed packs without any major deterioration in sensory quality parameters accept little increase in moisture.